2020
DOI: 10.21750/refor.9.01.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on seed germination of two Callistemon species (Myrtaceae)

Abstract: The genus Callistemon belongs to the family Myrtaceae and comprises 34 species. They are woody aromatic trees or shrubs that are widely distributed in the wet tropics. According to the scientific literature, research on seed germination of this genus was rarely carried out. The germination requirements of Callistemon citrinus and Callistemon linearis were studied under controlled conditions in the laboratory. Seeds of both species were tested for germination at constant temperatures of 25°C, 30°C, 40°C, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Table 1 shows the influence of temperature on the germination kinetics of S. stellata seeds, with three stages: a first period of latency owing to imbibition, a second exponential period during which germination is accelerated, and finally a stationary phase. The distinctive behavior of S. stellata revealed that temperature had a substantial (p< 0.001) impact on seed germination potential.The temperature may affect the rate of germination by breaking dormancy and induce the germination process (Kigel, 2017;Kheloufi et al, 2020). Seed germination of S. stellata has been affected (p< 0.001) by temperature regimes and the number of days to count (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the influence of temperature on the germination kinetics of S. stellata seeds, with three stages: a first period of latency owing to imbibition, a second exponential period during which germination is accelerated, and finally a stationary phase. The distinctive behavior of S. stellata revealed that temperature had a substantial (p< 0.001) impact on seed germination potential.The temperature may affect the rate of germination by breaking dormancy and induce the germination process (Kigel, 2017;Kheloufi et al, 2020). Seed germination of S. stellata has been affected (p< 0.001) by temperature regimes and the number of days to count (Tab.…”
Section: Resultsmentioning
confidence: 99%